The Impacts of Climate Change on Food Security and Livelihoods in Karamoja - Chaplin, Daniel; Byekwaso, Flavia; Semambo, Medi; Mujuni, Godfrey; Bantaze, James; Nyasimi, Mary; Wabyona, Edgar; Krishnaswamy, Siddharth (2017)
Karamoja’s population is highly dependent on subsistence agriculture, which is sensitive to climate conditions, making agriculture one of the most vulnerable sectors to the impacts of climate change. As a result, the region suffers chronic food insecurity due to the combined impacts of high levels of poverty, low human development and unfavourable climatic and weather conditions. However, little is known about the impacts of climate change on household food security, and in particular, the ability of households to adapt to Executive Summary climate change over time. This has resulted in gaps in food security and resilience programming. The objective of this study is therefore to contribute to, and facilitate, efforts in mainstreaming climate change adaptation into broader resilience programming initiatives and to identify appropriate adaptation policies and programmes that support the most vulnerable and food insecure communities in the Karamoja region.